Identification and quantification of subsidies relevant to the production of local and imported pig breeds in Vietnam - Drucker, Adam G.; Bergeron, E.; Lemke, U.; Thuy, L.T.; Valle-Zárate, A. (Springer, 2006)
Livestock diversity contributes in many ways to human survival and well-being, while its loss reduces options for attaining sustainable agriculture and universal food security. The current rapid rate of loss of this diversity is the result of a number of underlying factors. While in some cases changes in production systems and consumer preferences reflect the natural evolution of developing economies and markets, in other cases production systems, breed choice and consumer preferences have been distorted by local, national and international policy. In the context of a widespread threat to local pig breeds in Vietnam, this paper identifies and quantifies the level of agricultural subsidies that are currently contributing to this process of breed substitution. Producer subsidies—which tend to improve the competitiveness of imported breeds and their crosses over local breeds—are shown to be considerable, and mitigating measures are now urgently needed to avoid an irreversible loss of livestock diversity.